Currently recognized genes for schizophrenia: High‐resolution chromosome ideogram representation. Issue 2 (13th October 2015) - Butler, Merlin G.; McGuire, Austen B.; Masoud, Humaira; Manzardo, Ann M.
Abstract : A large body of genetic data from schizophrenia‐related research has identified an assortment of genes and disturbed pathways supporting involvement of complex genetic components for schizophrenia spectrum and other psychotic disorders. Advances in genetic technology and expanding studies with searchable genomic databases have led to multiple published reports, allowing us to compile a master list of known, clinically relevant, or susceptibility genes contributing to schizophrenia. We searched key words related to schizophrenia and genetics from peer‐reviewed medical literature sources, authoritative public access psychiatric websites and genomic databases dedicated to gene discovery and characterization of schizophrenia. Our list of 560 genes were arranged in alphabetical order in tabular form with gene symbols placed on high‐resolution human chromosome ideograms. Genome wide pathway analysis using GeneAnalytics was carried out on the resulting list of genes to assess the underlying genetic architecture for schizophrenia. Recognized genes of clinical relevance, susceptibility or causation impact a broad range of biological pathways and mechanisms including ion channels (e.g., CACNA1B, CACNA1C, CACNA1H ), metabolism (e.g., CYP1A2, CYP2C19, CYP2D6 ), multiple targets of neurotransmitter pathways impacting dopamine, GABA, glutamate, and serotonin function, brain development (e.g., NRG1, RELN ), signaling peptides (e.g., PIK3CA, PIK4CA ) and immune function (e.g., HLA‐DRB1, HLA‐DQA1 ) and interleukins (e.g., IL1A, IL10, IL6 ). This summary will enable clinical and laboratory geneticists, genetic counselors, and other clinicians to access convenient pictorial images of the distribution and location of contributing genes to inform diagnosis and gene‐based treatment as well as provide risk estimates for genetic counseling of families with affected relatives. © 2015 Wiley Periodicals, Inc.